Charismatic Economies: Pentecostalism, Economic Restructuring, and Social Reproduction - Barker, Isabelle V. (New Political Science, 2007)
Pentecostalism is one of the world's fastest growing religions, expanding most quickly in Latin America, sub-Saharan Africa, and parts of Asia. To make sense of this expansion in so many developing regions, I suggest that Pentecostalism fosters norms and behaviors that harmonize with neoliberal economic restructuring. I frame this theoretically with Polanyi's notion of double movement. In our current era of weakened state governance vis-à-vis neoliberal trade and fiscal policy, non-state sites of reaction have emerged. Pentecostalism is one such site, and, in contrast with Polanyi's example, I suggest that Pentecostalism has embedded the self-regulated aspects of neoliberal capitalism. I make this argument by using the feminist political economy theorization of social reproduction to interpret a number of empirical studies of Pentecostalism. Pentecostalism addresses dilemmas of social reproduction engendered by neoliberalism, and so may be said to embed this form of economic organization in human social life in a way that reinforces neoliberal capitalism.
Political Science
Keywords: Pentecostalism; capitalism; double movement; economic systems; economics; neoliberalism; social interaction; social reproduction; social structure; socialization